Make an ethical difference : tools for better action - Pastin, Mark, 1944- (BK business book., 2013)
People are often skeptical that there is anything they can do to raise society's ethical level. Mark Pastin begs to differ. We can make a difference, and we don't need ethics "experts" to tell us what to do. He argues that we all have an innate ethical sense--what he calls an "ethics eye." He offers tools for sharpening the ethics eye so we can see and do the right thing ourselves, particularly in the workplace, where our decisions can affect not just ourselves but coworkers, clients, customers, and even an entire organization. Seeing what's right is one thing--getting others to agree with you is another. With examples drawn from his decades of experience advising governments, corporations, and NGOs, Pastin shows how to identify competing interests, analyze the facts, understand the viewpoints, measure the benefits of different outcomes, and build consensus. You'll gain confidence in your ethical sense, make better leadership decisions, and take actions that elevate the ethics of the groups and organizations you belong to--and society as a whole."I know no one who has accomplished more than Pastin across the entire operations of ethical behavior. Enjoy his book, embrace his vision, adhere to his basic values and we will be a more ethical society."--Joe Rocks, CEO, NHS Human Services"Mark Pastin has written the only book on ethics that is worth reading."--Ian I. Mitroff, Professor Emeritus, Marshall School of Business, USC"Pastin continues to take ethics to the next level using examples to make the book not only interesting but also actionable and pragmatic."--Tony Spezia, President and CEO, Covenant Health